Iodine doping effects on the lattice thermal conductivity of oxidized polyacetylene nanofibers - Bi, Kedong; Weathers, Annie; Matsushita, Satoshi; Pettes, Michael T.; Goh, Munju; Akagi, Kazuo; Shi, Li (AMER INST PHYSICS, 2013)
Thermal transport in oxidized polyacetylene (PA) nanofibers with diameters in the range between 74 and 126 nm is measured with the use of a suspended micro heater device. With the error due to both radiation and contact thermal resistance corrected via a differential measurement procedure, the obtained thermal conductivity of oxidized PA nanofibers varies in the range between 0.84 and 1.24Wm(-1) K-1 near room temperature, and decreases by 40%-70% after iodine doping. It is also found that the thermal conductivity of oxidized PA nanofibers increases with temperature between 100 and 350 K. Because of exposure to oxygen during sample preparation, the PA nanofibers are oxidized to be electrically insulating before and after iodine doping. The measurement results reveal that iodine doping can result in enhanced lattice disorder and reduced lattice thermal conductivity of PA nanofibers. If the oxidation issue can be addressed via further research to increase the electrical conductivity via doping, the observed suppressed lattice thermal conductivity in doped polymer nanofibers can be useful for the development of such conducting polymer nanostructures for thermoelectric energy conversion. (C) 2013 AIP Publishing LLC.
Keywords: POLYMER; MODULUS; PURE